Bibliometric Analysis, Evolution and Trends of Happiness Management in Scientific Literature - Rando-Cueto, Dolores; Núñez-Sánchez, José-Manuel; Fernández-Díaz, Elena; De-las-Heras-Pedrosa, Carlos (ANDULI, Revista Andaluza de Ciencias Sociales, 2023)
This study aims to analyze the concept of "Happiness management" in the scientific literature that has resulted in recent research growing from interest in aspects related to happiness management in the social and professional spheres. A systematic review of publications is done to examine the current situation in terms of scientific production, and to analyze the evolution and trends of happiness management as presented in the scientific literature. In addition, using the Scopus database and the VOS viewer software, records were obtained from which a bibliometric analysis was done. Standing out among the results is the positioning of Spain as a benchmark country in the international literature on "Happiness management", and the influence of COVID-19 on the spread and citation of publications. Scientific contributions on this subject and their influence on future research is a growing field of study and of interest in the improvement of quality of life and organizational well-being.